QSAR Analysis of Rocaglamide Derivatives Cytotoxic Activities Using LFER Hansch Model - Firdayani Firdayani; Susi Kusumaningrum; Doddy Irawan Setyo Utomo; Agung Eru Wibowo; Chaidir Chaidir (Indonesian Society for Cancer Chemoprevention, 2010)
Rocaglamide derivatives are the compounds which have featuring cyclopenta[b]tetra-hydrobenzofuran skeleton. Until now it includes more than 50 naturally occurring derivatives. They were chosen to be interesting candidates for possible therapeutic agents primarily in the field of cancer chemotherapy due to their cytotoxic activities data against various cancer cells. A quantitative structure activity relationship (QSAR) studies were done to investigate physicochemical properties of molecule which contribute to their activities. Series of rocaglamide derivatives have been used and analyzed using linear free energy regression Hansch model for their cytotoxic activities against MONO-MAC-6 leukemia cells, RAJI lymphoma cells and MEL-JUSO melanoma cells. Results showed that the best QSAR equations were revealed involving C Log P and CMR parameters with nonlinear regression relationships in cytotoxic activities of rocaglamide derivatives against cancer cells above. Keywords: QSAR, Rocaglamide, LFER Hansch